Family Communication Patterns in Early Marriage - Aziz Taufik Hirzi; Nenny Kencanawati; Fadhli Muttaqien; Vera Martikasari; Euis Evi Puspitasari; Ijang Faisal (UIN Sunan Gunung Djati Bandung, 2022)
Families in Siderang Legok, Cintanagara Village, Cigedug District, Garut Regency, which have family members between 6-14 people, are used to marrying off their children at a young age under the terms of the Marriage Law. This study aims to obtain data and information about internal family communication patterns which consist of causes of early marriage and high childbirth rates; the role of the government and related parties and the daily life of local families in caring for several children. The research method is qualitative with a case study approach. While the subject of research is the head of the family/deputy head of the family as actors, assisted by village officials who understand the actual conditions of the local community. The theory used is prophetic communication consisting of (1) Humanization, (2) Liberation, and, (3) Transcendence. The results of the study show that marriage at an early age which has an impact on childbirth rates is a normal matter as part of an effort to humanize humans because early marriage is better than free association with people of different sexes. Then, the government, through the BKKBN and village apparatus, who have tried their best, have failed to get significant results. Family planning continues, early marriage is still ongoing, and the birth rate is still high. What is unique, their daily life looks as usual, does not seem worried or restless. They are used to having many children and feel obligated to care for them, which is strengthened by a religious atmosphere that makes religion (Islam) the mainstay. The conclusion is that in the Siderang Legok family environment, there are no worries about getting married at an early age and having many children, because once you are married, whatever happens, you have to be ready to face it. Appeals and assistance from the government and related parties are still being followed even though the results achieved are not satisfactory. Then the back of religion ranks first.